Influence of ATP-binding cassette transporter 1 R219K and M883I polymorphisms on development of atherosclerosis: a meta-analysis of 58 studies. - Yan-Wei Yin; Jing-Cheng Li; Dong Gao; Yan-Xiu Chen; Bing-Hu Li; Jing-Zhou Wang; Yun Liu; Shao-Qiong Liao; Ming-Jie Zhang; Chang-Yue Gao; Li-Li Zhang (PLoS ONE, 2014)
BACKGROUND: Numerous epidemiological studies have evaluated the associations between ATP-binding cassette transporter 1 (ABCA1) R219K (rs2230806) and M883I (rs4149313) polymorphisms and atherosclerosis (AS), but results remain controversial. The purpose of the present study is to investigate whether these two polymorphisms facilitate the susceptibility to AS using a meta-analysis. METHODS: PubMed, Embase, Web of Science, Medline, Cochrane database, Clinicaltrials.gov, Current Controlled Trials, Chinese Clinical Trial Registry, CBMdisc, CNKI, Google Scholar and Baidu Library were searched to get the genetic association studies. All statistical analyses were done with Stata 11.0. RESULTS: Forty-seven articles involving 58 studies were included in the final meta-analysis. For the ABCA1 R219K polymorphism, 42 studies involving 12,551 AS cases and 19,548 controls were combined showing significant association between this variant and AS risk (for K allele vs. R allele: OR = 0.77, 95% CI = 0.71-0.84, P<0.01; for K/K vs. R/R: OR = 0.60, 95% CI = 0.51-0.71, P<0.01; for K/K vs. R/K+R/R: OR = 0.69, 95% CI = 0.60-0.80, P<0.01; for K/K+R/K vs. R/R: OR = 0.74, 95% CI = 0.66-0.83, P<0.01). For the ABCA1 M883I polymorphism, 16 studies involving 4,224 AS cases and 3,462 controls were combined. There was also significant association between the variant and AS risk (for I allele vs. M allele: OR = 0.85, 95% CI = 0.77-0.95, P<0.01). CONCLUSIONS: The present meta-analysis suggested that the ABCA1 R219K and M883I polymorphisms were associated with the susceptibility to AS. However, due to the high heterogeneity in the meta-analysis, the results should be interpreted with caution.